The emerging role of regulatory cell-based therapy in autoimmune disease - Ghobadinezhad, Farbod; Ebrahimi, Nasim; Mozaffari, Fatemeh; Moradi, Neda; Beiranvand, Sheida; Pournazari, Mehran; Rezaei-Tazangi, Fatemeh; Khorram, Roya; Afshinpour, Maral; Robino, Rob A.; Aref, Amir Reza; Ferreira, Leonardo M. R. (Frontiers in Immunology, 2022)
Autoimmune disease, caused by unwanted immune responses to self-antigens, affects millions of people each year and poses a great social and economic burden to individuals and communities. In the course of autoimmune disorders, including rheumatoid arthritis, systemic lupus erythematosus, type 1 diabetes mellitus, and multiple sclerosis, disturbances in the balance between the immune response against harmful agents and tolerance towards self-antigens lead to an immune response against self-tissues. In recent years, various regulatory immune cells have been identified. Disruptions in the quality, quantity, and function of these cells have been implicated in autoimmune disease development. Therefore, targeting or engineering these cells is a promising therapeutic for different autoimmune diseases. Regulatory T cells, regulatory B cells, regulatory dendritic cells, myeloid suppressor cells, and some subsets of innate lymphoid cells are arising as important players among this class of cells. Here, we review the roles of each suppressive cell type in the immune system during homeostasis and in the development of autoimmunity. Moreover, we discuss the current and future therapeutic potential of each one of these cell types for autoimmune diseases.